Influence of laser absorptivity of CuCr0.8 substrate surface state on the characteristics of laser directed energy deposition inconel 718 single track - Baopeng Zhang; Haifeng Xiao; Weicheng Wang; Feiyang Li; Yun Wang; Haihong Zhu (Journal of Materials Research and Technology)
An effective method for fabricating copper-nickel bimetallic liquid rocket engine thrust chambers involves utilizing laser directed energy deposition (LDED) technology. However, the state of the substrate surface significantly impacts the LDED process. This study investigates the effects of various substrate treatments on LDED single tracks, using CuCr0.8 high-copper alloy as the substrate and Inconel 718 as the deposition material. The treatments include polishing, sandblasting, laser etching, and cold spraying. Substrate surface roughness, laser absorptivity, molten pool morphology, and microstructure were characterized, and the mechanisms of laser absorptivity change and the different LDED processes were analyzed. The results indicate that the laser-etched surface exhibits the worst surface roughness (Ra 15.20 ± 0.60 μm), the highest laser absorptivity(80.70% at 1080 nm wavelength), the largest deposition width (947.33 ± 29.85 μm), and the maximum number of fine grains among the four substrates. Additionally, the cold-sprayed surface shows the largest deposition depth (237.33 ± 39.04 μm), the minimum number of fine grains and a higher laser absorptivity (66.20% at 1080 nm wavelength). In situ observations of molten pool formation and flow during LDED was conducted using an in situ high-speed high-resolution imaging system. The mechanisms underlying the alteration in laser absorptivity primarily involve the ''trapped light'' effect and modifications to the surface material. This research is significant as it provides foundational insights for laser processing of highly reflective materials, offering important theoretical and practical implications for engineering applications.